Predictive value of patent foramen ovale diameter for cryptogenic stroke and age-related differences - Wang, Rui; Qiao, Miao; Song, Guanghui; Wang, Wei; Yang, Liuyin; Lin, Zhenzhen; Meng, Lingcui (Frontiers in Cardiovascular Medicine, 2025)
IntroductionPatent foramen ovale (PFO) is associated with cryptogenic stroke (CS), whereas not all PFO carriers experience strokes. Current risk assessment tools like the Risk of Paradoxical Embolism (RoPE) scoring system and PFO-Associated Stroke Causal Likelihood (PASCAL) system have limitations, particularly in elderly populations. This study aims to explore risk factors for PFO-related CS and evaluate age-related differences between younger and elderly patients.MethodsThis retrospective study included 344 patients with PFO, categorized into no stroke (NS), cryptogenic stroke (CS), and non-cryptogenic stroke (NCS) groups. Demographic, clinical, laboratory, and detailed PFO anatomical data were collected. Multivariate logistic regression and ROC analysis identified independent risk factors and optimal PFO diameter cut-off. Age subgroup analyses were performed.Results17.2% of PFO patients were found to have CS. The mean PFO diameter was significantly larger in CS (2.54 ± 0.79 mm) compared to NS (1.70 ± 0.73 mm) and NCS (1.98 ± 1.10 mm; P < 0.05). Multivariate analysis confirmed PFO diameter as an independent CS risk factor (CS vs. NS: OR = 2.215, P = 0.001; CS vs. NCS: OR = 1.554, P = 0.028). ROC analysis demonstrated good predictive accuracy for CS (AUC = 0.773), with an optimal cut-off of 1.75 mm. Elevated white blood cell count (WBC), age ≥ 60 years, large right-to-left shunt (RLS), previous stroke/transient ischemic attack (TIA) and cortical infarction were associated with CS. Age subgroup analysis showed heterogeneity: in younger patients (<60 years), PFO diameter exhibited predictive capacity (AUC = 0.777, cut-off value = 1.75 mm) but lacked statistical significance in regression analysis (P > 0.05). Large RLS exhibited a risk factor (OR = 7.576, P = 0.099). Conversely, among elderly patients (≥60 years), PFO diameter remained a significant predictor (higher cut-off: 1.95 mm; AUC = 0.767), and smoking (OR = 5.26, P = 0.043) emerged an additional risk factor.ConclusionCS was present in 17.2% of PFO patients. An enlarged diameter of PFO (optimal cut-off value: 1.75 mm in overall and younger; 1.95 mm in elderly) is a crucial anatomical risk factor. Elevated WBC, large RLS, previous stroke/TIA and cortical infarction are also correlated with CS. Age subgroup analysis revealed heterogeneity: PFO anatomy (diameter, RLS) is primary in younger patients, whereas in elderly patients (≥60 years), both PFO anatomy and systemic factors (smoking) should be considered.